Primary prophylaxis of invasive fungal infections in patients with haematologic malignancies. 2014 update of the recommendations of the Infectious Diseases Working Party of the German Society for Haematology and Oncology - Tacke, Daniela; Buchheidt, Dieter; Karthaus, Meinolf; Krause, Stefan; Maschmeyer, Georg; Neumann, Silke; Ostermann, Helmut; Penack, Olaf; Rieger, Christina; Ruhnke, Markus; Sandherr, Michael; Schweer, Katharina E.; et al. (Annals of Hematology, 2014)
Invasive fungal infections cause substantial morbidity and mortality in immunocompromised patients, particularly in those with haematological malignancies and recipients of allogeneic haematopoietic stem cell transplantation. Difficulties in diagnosing invasive fungal infections and subsequent delays in treatment initiation lead to unfavourable outcomes and emphasise the importance of prophylaxis. Since the recommendations of the Infectious Diseases Working Party of the German Society for Haematology and Oncology in 2009, results of 14 additional clinical studies have been published comprising 2,899 patients and initiating this update. Key recommendations for adult patients are as follows: Posaconazole remains the drug of choice during remission-induction chemotherapy in acute myeloid leukaemia, myelodysplastic syndrome and allogeneic haematopoietic stem cell transplantation with graft versus host disease (AI). In the pre-engraftment period of allogeneic transplantation, several antifungals are appropriate and can be recommended with equal strength: voriconazole (BI), micafungin (BI), fluconazole (BI) and posaconazole (BII). There is poor evidence regarding antifungal prophylaxis in the post-engraftment period of allogeneic haematopoietic stem cell transplantation if no steroids for treatment of graft versus host disease are required. Aerosolised liposomal amphotericin B inhalation in conjunction with fluconazole can be used in patients with prolonged neutropenia (BII).
EVALuna2:25698